2015
DOI: 10.1039/c5fo00607d
|View full text |Cite
|
Sign up to set email alerts
|

Curcumenol isolated from Curcuma zedoaria suppresses Akt-mediated NF-κB activation and p38 MAPK signaling pathway in LPS-stimulated BV-2 microglial cells

Abstract: Curcumenol, a sesquiterpene isolated from Curcuma zedoaria is known to possess a variety of health and medicinal values which includes neuroprotection, anti-inflammatory, anti-tumor and hepatoprotective activities. The current study aim is to investigate the modulatory effects of curcumenol towards the lipopolysaccharides (LPS)-induced inflammation in BV-2 microglia. Curcumenol markedly decreased LPS-induced production of nitric oxide (NO), pro-inflammatory cytokines [(IL-6) and (TNF-α)] and pro-inflammatory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…Thus, most of the anti-inflammatory drugs were found to modulate iNOS and COX-2 via inhibit NF-κB and p38 signaling. For instance, resveratrol and curcumenol, natural plant derivatives, suppressed iNOS and COX-2 via inhibition of NF-κB and p38 signaling pathways (Zhong et al, 2012; Lo et al, 2015). This is concordant with our current findings which demonstrated that treatment with ESEAF suppressed the phosphorylation of p38 by attenuating the translocation of NF-κB along with the alteration of iNOS and COX-2 upon stimulation of LPS in microglia cells, suggesting that ESEAF is a potent inhibitor of p38.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most of the anti-inflammatory drugs were found to modulate iNOS and COX-2 via inhibit NF-κB and p38 signaling. For instance, resveratrol and curcumenol, natural plant derivatives, suppressed iNOS and COX-2 via inhibition of NF-κB and p38 signaling pathways (Zhong et al, 2012; Lo et al, 2015). This is concordant with our current findings which demonstrated that treatment with ESEAF suppressed the phosphorylation of p38 by attenuating the translocation of NF-κB along with the alteration of iNOS and COX-2 upon stimulation of LPS in microglia cells, suggesting that ESEAF is a potent inhibitor of p38.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivated microglia produce large amounts of inflammatory molecules and promote neuronal death (1315). Furthermore, microglial activation is correlated with sequential signaling pathways, including NF-κB and MAPK cascades, thus leading to the expression and production of proinflammatory mediators (16). …”
Section: Discussionmentioning
confidence: 99%
“…In response to inflammatory stimuli, IκB phosphorylation and degradation lead to the release of NF-κB dimers into the nucleus, thus expressing specific target genes, such as pro-inflammatory cytokines, inducible nitric oxide synthase (iNOS), and the cyclooxygenase-2 (COX-2) protein [7]. Moreover, the three mitogen-activated protein kinase (MAPK) signaling pathways consisting of c-Jun NH2-terminal kinase (JNK), p38 and extracellular signal-regulated kinase (ERK) also modulate microglial inflammatory responses through the regulation of downstream cellular targets, including NF-κB pathway [8]. In addition, the phosphatidyl inositol 3-kinase/Akt (PI3K/Akt) pathway plays an essential role in the activation of NF-κB and subsequent up-regulation of inflammatory genes expression [8,9].…”
Section: Introductionmentioning
confidence: 99%